Penerapan Model Pembelajaran Argument Driven Inquiry (ADI) Untuk Meningkatkan Hasil Belajar IPA dan Keterampilan Argumentasi Peserta Didik Kelas VIII SMP Negeri 14 Kendari pada Materi Usaha dan Pesawat Sederhana - Asriani, Asriani; M, Hunaidah; Erniwati, Erniwati (Universitas Halu Oleo, 2021)
This study aims to determine the differences and increase in science learning outcomes and argumentation skills of students on business materials and simple aircraft for class VIII SMP Negeri 14 Kendari who learn through the Argument Driven Inquiry (ADI) learning model. The method used was the research instrument in the form of a science learning achievement test and argumentation skills test. The research data were analyzed using descriptive and inferential statistics. The results of the study: 1) there is no significant difference between the pre-test mean value of learning outcomes in science learning through the ADI learning model and the scientific approach based on a significance value of 0.414; 2) there is no significant difference between the pre-test mean value of argumentation skills learned through the ADI learning model and the scientific approach based on a significance value of 0.523; 3) the average post-test score of science learning outcomes in the experimental class is 82.14; 4) the post-test average score of the experimental class students' argumentation skills was 78.29; 5) the average N-Gain value of the experimental class students' science learning outcomes was 0.71; and 6) the average value of N-Gain argumentation skills of experimental class students was 0.7. These results indicate that teaching using the ADI learning model can improve science learning outcomes and argumentation skills of class VIII students of SMP Negeri 14 Kendari.